„W krainę dziecka. Rzecz o uroku dziecięctwa” na materiałach ikonograficznych z II połowy XIX i początku XX wieku – wybrane problemy - Nawrot-Borowska, Monika (Studia Edukacyjne, 2018)
The present text is the second part of the author’s description of iconographic sources for studying the history of a child and childhood in the second half of 19th and the beginning of 20th century. In the former, the types of sources addressed to children were discussed, in which the researcher will find “pictures from the children’s world”. It showed examples of iconographic materials presenting children in various everyday and festal situations, published in the richly illustrated children’s press, fairy tales, stories, collections of literary pictures, poems, fettered speeches, illustrated primers and visual boards for the science of things. The subject of these findings is the child and childhood shown in iconographic materials in the second half of 19th and the beginning of 20th century. During this period, as a result of the ongoing civilizational, technological and cultural changes, a significant increase in the types and number of publications illustrated with graphics, and later also with photographs can be observed. The press is being developed, including the illustrated, women’s, family, socio-literary, everyday press, both on a general and regional scale. Also, numerous calendars are being published, including their illustrated versions. Daguerreotype is becoming popular while correspondence with the use of postcards is popularized. All these sources will be used as the source basis for the text, for the purpose of characterizing the iconographic materials depicting the children’s world. When analyzing the iconographic material in terms of history and pedagogy, the researcher of the history of childhood can find many interesting aspects. He or she can observe scenes from children’s lives, including family life, education (home and school education), relationships with adults and peers, undertaken pursuits, everyday activities, behaviors, ways of spending time, fun and pastimes. On their basis, the researcher can describe children’s appearance, dress, hairdo, toys, interiors, the surroundings in which they stayed and the equipment they used, which make up the material aspects of the children’s world. The particular types of iconographic sources will be presented below, where the researcher can find the scenes of childhood. In addition to discussing their specificity, the provided examples will illustrate the everyday life present in a given type of iconographic material.